2018
DOI: 10.1109/lawp.2018.2834981
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order-Mode Circularly Polarized Two-Layer Rectangular Dielectric Resonator Antenna

Abstract: This is a repository copy of Higher order mode circularly polarized two-layer rectangular dielectric resonator antenna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…It is also reported that modified single feeding technique has utilized for the generation of better CP bandwidths like the modified shape of microstrip feed with modified slot has been reported in Ref. , and by using logarithmic spiral slots in the ground with LED and excited by coaxial probe …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that modified single feeding technique has utilized for the generation of better CP bandwidths like the modified shape of microstrip feed with modified slot has been reported in Ref. , and by using logarithmic spiral slots in the ground with LED and excited by coaxial probe …”
Section: Introductionmentioning
confidence: 99%
“…14, and by using logarithmic spiral slots in the ground with LED and excited by coaxial probe. 15 In this article, a coaxial probe feeding is used to generate the CP radiation in an asymmetric cross-shaped dielectric resonator antenna. Here, the shapes of the dielectric resonator have been playing an important role in obtaining the circularly polarized radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Some other feeding networks like single feed, off‐centered microstrip integrated with DRA and modified microstrip feed network DRA are capable of offering circular polarization. In Reference higher order circular polarized DRA, DRA with Fabry Perot high‐Gain circularly polarization, DRA array fed by the Cavity‐Backed SIW, high gain self‐package used in DRA have been explored. Recently reconfigurable circular polarized liquid dielectric resonator and a low profile multilayer cylindrical segment fractal DRA have been investigated for wideband applications.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth is to add metallic strips onto DRAs' side walls [11,12]. And the last is to modify the coupling aperture embedded on the ground plane [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The aperture-coupling excitation method with a microstrip feed-line has the advantage of having the feed network located below the ground plane, thus avoiding spurious radiation and the advantage of integrating DRAs with printed feed structures [38]. Therefore, this excitation method has usually been used to excite the DRAs [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,39] and the last method of designing a single-feed CP DRA (modifying the coupling aperture embedded on the ground plane) is the most popular one by designers. There are many kinds of modified coupling apertures used to design single-feed CP DRAs.…”
Section: Introductionmentioning
confidence: 99%